Dietrich i von Mörs (1226-1262) Ejemplo paradigmático de la nueva nobleza medieval alemana tras los tiempos de Inocencio III = Dietrich I von Mörs (1226-1262) : Paradigmatic example of the new medieval German nobility after the era of Innocent III - Sancho Gómez, Miguel (2016)
One of the most important aspects of the foreign policy concerning Pope Innocent III was his relationship with the Empire; as great jurist and expert in theology himself, he began a movement by which he was considered guardian and defender of the souls of all Christendom, while the lay princes were only the way of physical defense of his subjects. He reserved the right to intervene in politics in Christian lands, and respecting the capacity of Electors (three of which were in turn princes of the Church) he stated his right to ratify that choice (or not), as the Empire itself came in principle and by their own motivation, from the Church. Thus, after the death of Henry VI in 1197, Innocent III imposed his great authority to establish himself as referee and judge of the pretenders to the throne. The subsequent conflict between the already usurper Otto IV and Philip Augustus of France (Battle of Bouvines, 1214), definitely transformed the relations between Papacy and Empire, leaving deep footprints in the German lands and a political and institutional setting that we propose to demarcate with the illustrative example of the counts of Mörs.
Keywords: Innocent III; German Empire; Moers county; Investitures; German middle ages; Papacy